1996
DOI: 10.1097/00004647-199601000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Simulation Study of Cerebral Arteriovenous Malformations. Part 2. Effects of Impaired Autoregulation and Induced Hypotension

Abstract: Summary:The hemodynamic changes occurring during obliteration procedures for arteriovenous malformations (AVM) have not been fully elucidated, Therefore, we un dertook a simulation study using a compartmental flow model to investigate the role of altered autoregulatory conditions in the development of hyperperfusion during obliteration of large high-flow A VM. Induced hypoten sion was also simulated to evaluate its usefulness in re ducing the incidence and severity of the event. As the A VM flow was decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 24 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…93 Biomathematical models based on electrical network analysis have been developed and used to theoretically evaluate the hemodynamics within an AVM nidus. [30][31][32]34,[48][49][50]63,70 In a study of the risk of AVM rupture due to venous outflow obstruction, the investigators have found that stenosis or occlusion of a high-flow draining vein is predictive of an AVM rupture. 31 An acute alteration in cerebral hemodynamics following resection of an AVM is a known cause of postoperative hemorrhage.…”
Section: Hemodynamic Alterations and Avm Hemorrhagementioning
confidence: 99%
“…93 Biomathematical models based on electrical network analysis have been developed and used to theoretically evaluate the hemodynamics within an AVM nidus. [30][31][32]34,[48][49][50]63,70 In a study of the risk of AVM rupture due to venous outflow obstruction, the investigators have found that stenosis or occlusion of a high-flow draining vein is predictive of an AVM rupture. 31 An acute alteration in cerebral hemodynamics following resection of an AVM is a known cause of postoperative hemorrhage.…”
Section: Hemodynamic Alterations and Avm Hemorrhagementioning
confidence: 99%
“…Therapeutic embolisation encompasses a staged approach to the reduction and elimination of arteriovenous flow with its own risks but avoids the risks associated with open surgery 2 . Potential risks of embolisation include glue injection into the normal cortical vascular branches, passage into draining veins with the risk of swelling of or rupture and bleeding from the AVM and gluing of the catheter into the vessel being embolised 3,6,7 . Symptomatic pulmonary complications have been reported following acrylate glue injection, particularly when delivery systems without flow arrest were used in high flow vascular lesions 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical compression and edema around the brain tumor 8, 16,24) and altered blood flow around the vascular lesion 13,19,23,26,33) may Task-Related Signal Decrease on fMR Imaging result in less increase in rCBF due to neuronal activation in the pathologic brain than in the normal brain. Regional deoxy-Hb increases as a result of neuronal activation and oxygen consumption, whereas blood flow-related oxy-Hb supply does not increase so much, leading to an increase in the magnetic susceptibility effect, which produces a task-related signal reduction on fMR imaging.…”
Section: Discussionmentioning
confidence: 99%